2023
DOI: 10.1038/s41598-023-34590-1
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and high-efficiency polarization conversion with a nano-kirigami based metasurface

Abstract: Nano-kirigami metasurfaces have attracted increasing attention due to their ease of three-dimension (3D) nanofabrication, versatile shape transformations, appealing manipulation capabilities and rich potential applications in nanophotonic devices. Through adding an out-of-plane degree of freedom to the double split-ring resonators (DSRR) by using nano-kirigami method, in this work we demonstrate the broadband and high-efficiency linear polarization conversion in the near-infrared wavelength band. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Many potential applications of metasurfaces, such as beam steering, lensing, holography or structured light generation would require full 2π phase control [15][16][17][18][19][20][21][22][23][24][25][26]. However, in the concept of digital metasurfaces, it has been shown that by employing binary or 1-bit ('0' and '1') elements with only π phase shift it is possible to achieve beam steering (see e.g.…”
Section: Optical Design Of the Reprogrammable Metasurface Beam Steerermentioning
confidence: 99%
See 1 more Smart Citation
“…Many potential applications of metasurfaces, such as beam steering, lensing, holography or structured light generation would require full 2π phase control [15][16][17][18][19][20][21][22][23][24][25][26]. However, in the concept of digital metasurfaces, it has been shown that by employing binary or 1-bit ('0' and '1') elements with only π phase shift it is possible to achieve beam steering (see e.g.…”
Section: Optical Design Of the Reprogrammable Metasurface Beam Steerermentioning
confidence: 99%
“…This field investigates the potential applications of metasurfaces in developing compact optical components [18][19][20]. To date, phased array metasurfaces have been used to realize different categories of flat devices, namely beam splitters [17][18][19][20], focusing mirrors [21,22], focusing lenses [23], holograms [24], and polarization converters [25,26]. However, the aforementioned metasurfaces are passive, i.e.…”
Section: Introductionmentioning
confidence: 99%